Non-noble metal-based photoelectrocatalysts for green hydrogen production and water remediation - Sacco, Nicolás Alejandro (2025)
This work explores the development of NiMo-based materials supported on TiO2 for dual applications: photoelectrochemical green hydrogen production and degradation of paracetamol. Photoelectrocatalysts were synthesized by the wet impregnation method and calcined at 400 and 900 °C to assess the influence of thermal treatment on their properties. The catalyst calcined at 400 °C achieved higher hydrogen evolution efficiency, with current densities (j) over three times higher than those of the catalyst prepared at 900 °C, attributed to its larger surface area and photoelectrochemical properties. Both catalysts effectively degraded paracetamol under light irradiation. These findings demonstrate the potential of NiMo-TiO2 as a sustainable and cost-effective alternative to noble metal catalysts, combining environmental remediation with renewable energy production.